Kajian Literatur Faktor-Faktor yang Berhubungan dengan Peranan Kader Kesehatan dalam Penemuan Kasus TBC - Aisyah Farrah Yusri Pratama (Journal of Health and Therapy, 2021)
Background: The data on the discovery of tuberculosis cases in 2019 in Indonesia were 65% reported while 25% were not reported. This figure is still far from the target that has been set, which is 90%. One alternative that is appropriate for discovery is active community-based discovery, especially health cadres who have been equipped with knowledge and skills. Objective: The purpose of this study was to examine the factors associated with the role of health cadres in the discovery of tuberculosis cases. Methods: The method used is a literature review using 4 databases. Articles reviewed using cross-sectional research methods with population and samples are health cadres, must be indexed nationally and internationally, full text and published no more than 10 years. There are 6 articles studied. Results: From the 6 journals studied, it was stated that there was a significant relationship between knowledge, attitudes, motivation, providing incentives, providing training and support for health workers with the role of cadres in TB case finding. Conclusion: There are several factors that influence the role of cadres in TB case finding, but the research results are still very diverse due to the inaccuracy in the selection of statistical tests, data collection instruments and the number of samples.